Kinematic analysis and optimal design of three-legged reconfigurable parallel manipulators - Anjan Kumar Dash (2008)
The focus of this work is on a class of three-legged modular reconfigurable parallel manipulators having spherical end joints. In the study on instantaneous kinematics, easy generic and intuitive method of determine reciprocal screws based on POE scheme is proposed using twist annihilators.